New AODV Routing Method for Mobile Wireless Mesh Network (MWMN). Issue 3 (2nd July 2016) - Ma, Z.; Zhang, D. G.; Liu, S.; Li, W. B.
Abstract: Mobile Wireless Mesh Network (MWMN) consists of numerous wireless sensors, the energy and communication ability of which are limited, and they send the sensing data to the receivers through mutual cooperation. In the next generation of network, wireless mesh networks are expected to play a more important role in mobile applications. Multicast communication is an effective way to save energy, bandwidth, cost and other resources in MWMN, so we propose a new Extended Ad hoc On-Demand Distance Vector (EAODV) routing method of MWMN in this paper. The new EAODV routing method chooses the forwarding routes, which can connect more multicast receivers to solve routing optimization problems. The method proposes a dynamic strategy to change the multicast tree structure based on the characteristic of node mobility of wireless network. It tries to minimize the energy consumption to extend the lifetime of the network, while an energy-balanced routing method can help to make the network lifetime longer by using the energy in a balanced way. Simulation results demonstrate that our method effectively improves the efficiency of multicast routing, the advantage and novelty of the approach suggested is its good performance in many aspects of mobile applications.